Infrastructure development, income inequality, and urban sustainability in the People's Republic of China - Octasiano M. Valerio Mendoza (Asian Development Bank Institute (ADBI), 2017)
This paper examines the relationship between infrastructure development and income inequality in urban People's Republic of China. Recent policies target reductions in income inequality while increasing sustainable urban development. Infrastructure investment plays a key role in achieving both goals, yet the effects of different infrastructures on income disparities at the city level remain undetermined. Using 10 city-level infrastructure indicators relating to sustainable urban development and city income inequality measures, calculated using the China Household Income Project (CHIP) Surveys, this study investigates the correlation between infrastructure and inequality from 2005 to 2013. The results indicate that wastewater treatment, domestic waste management, public green spaces, water efficiency, and residential power efficiency infrastructures were negatively correlated with income inequality with a lag of 2 or 3 years. Investment in these infrastructures might be associated with reductions in inequality ranging from 4% to 49%. Conversely, mass transit usage was positively correlated with income inequality both 2 and 3 years later. An increase in mass transit ridership of 20 trips per capita annually might be associated with a 1% rise in income inequality after 2 years. Increase in water supply coverage and Internet access were also positively correlated with rising inequality. Investment in these infrastructures might warrant further measures to ensure adequate distributional outcomes.
Keywords: C33; H54; O18; D63; H30; R11; 330; income inequality; infrastructure; PRC; sustainable urban development